2010
DOI: 10.1007/s11481-010-9217-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Egr-1 Expression in Astrocytes by HIV-1 Tat: New Insights into Astrocyte-Mediated Tat Neurotoxicity

Abstract: Human immunodeficiency virus type 1 (HIV-1) Tat plays an important role in HIV-associated neuropathogenesis; the underlying mechanisms are still evolving. We have recently shown that HIV-1 Tat induces expression of glial fibrillary acidic protein (GFAP), a characteristic of HIV-1 infection of the central nervous system (CNS). We have also shown that the Tat-induced GFAP expression in astrocytes is regulated by p300, and that deletion of the early growth response 1 (Egr-1) cis-transacting element within the p30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 62 publications
7
34
0
Order By: Relevance
“…These findings suggested that cocaine-mediated activation of ERK and JNK MAPKs pathways were upstream of Egr-1. Interestingly, our findings are in agreement with a report from Fan et a l demonstrating that HIV Tat-mediated astrogliosis involves activation of Egr-1 and transcriptional upregulation of GFAP [7]. It is likey that Egr-1 is one of the common signaling molecules critical for both Tat and cocaine-mediated activation of astrocytes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings suggested that cocaine-mediated activation of ERK and JNK MAPKs pathways were upstream of Egr-1. Interestingly, our findings are in agreement with a report from Fan et a l demonstrating that HIV Tat-mediated astrogliosis involves activation of Egr-1 and transcriptional upregulation of GFAP [7]. It is likey that Egr-1 is one of the common signaling molecules critical for both Tat and cocaine-mediated activation of astrocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Since acute cocaine administration has been shown to elicit rapid and transient induction of several immediate-early genes in the brain, including Egr-1, c-fos and junB [30] and Egr-1 has been suggested to function as a molecular switch that coordinates changes in GFAP expression [31], we sought to examine whether cocaine-mediated induction of GFAP expression involved activation of Egr-1 in astrocytes. As shown in Figure 4a & b, cocaine up-regulated expression of Egr-1 in a time-dependent manner with peak expression elicited between 1–3h and a decline thereafter, both in A172 cells and in mouse primary astrocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies, including ours, have shown that astrocytes potentiate Tat neurotoxicity (16,20,22), probably through Tat-mediated transcriptional activation of glial fibrillary acidic protein (GFAP) expression (29 -31). Of particular note is that Tat expression in astrocytes alone is sufficient to induce pathological changes such as reactive astrocytes or astrocytosis, loss of neuron axons and dendrites, and neurobehavioral deficits such as impaired motor and cognitive functions in the CNS reminiscent of HIVassociated MCMD (22,29,32,33). These findings support the notion that astrocyte-mediated Tat neurotoxicity plays important roles in HIV/neuroAIDS.…”
supporting
confidence: 55%
“…ERCC1 plays a pivotal role in several DNA repair pathways and also forms a structure-specific heterodimeric endonuclease with xeroderma pigmentosum complementation group F, which cleaves damaged 5'-DNA in the lesion (Doll et al, 2010). Previous research has shown a strong association between the decrease in ERCC1 expression and the occurrence of cancer (Fan et al, 2011). The results of our study indicated that low ERCC1 expression was correlated with poor prognosis of EC, and SNX-2112 could be used to treat EC by increasing the expression of ERCC1.…”
Section: Discussionmentioning
confidence: 99%